2010
DOI: 10.1055/s-0029-1245833
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Contrast-Enhanced Harmonic Endoscopic Ultrasonography for the Discrimination of Solid Pancreatic Masses

Abstract: The majority of cases of both pancreatic adenocarcinoma and chronic pancreatitis were hypoenhanced and visual discrimination was not possible. This is the first study about CEH-EUS for the quantitative assessment of uptake after contrast injection which has shown that it can aid differentiation between benign and malignant masses but cannot replace EUS-FNA. Neither tumor stage nor therapeutic management have changed after contrast medium injection during CEH-EUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 25 publications
2
77
0
2
Order By: Relevance
“…A similarly low negative predictive value (64%) was found previously in a study using core biopsy and cytoblock preparation [6]. To increase this value, a higher number of passes [11], a proper selection of adequate material [6] or guidance under contrast enhancement can be performed [21]. Other reports showed that repeating the EUS-FNA in the case of an initially negative cytology increased the yield of diagnosis [25][26][27], as in our group of patients, where the diagnostic rate increased to 96%, despite some delay for obtaining the final diagnosis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A similarly low negative predictive value (64%) was found previously in a study using core biopsy and cytoblock preparation [6]. To increase this value, a higher number of passes [11], a proper selection of adequate material [6] or guidance under contrast enhancement can be performed [21]. Other reports showed that repeating the EUS-FNA in the case of an initially negative cytology increased the yield of diagnosis [25][26][27], as in our group of patients, where the diagnostic rate increased to 96%, despite some delay for obtaining the final diagnosis.…”
Section: Discussionmentioning
confidence: 53%
“…The sample quality for histological analysis (diagnostic cell clusters, appropriate architecture) differed between two experienced endosonographers, proving the importance of the technique in core sampling [6]. Previously, a diagnosis sensitivity rate of 60-73% by using another 22G needle [10,21,22] was obtained. Only one study used the same type of 22G FNA needle as we did, in a small number of patients; the procurement of core biopsy was 100%, but the optimal histological core was 66.7% [4].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative interpretation can be subjective, however, and quantification of contrast uptake is expected to yield new information with improved accuracy. We used a hue histogram analysis and noted that a hypoenhanced aspect can occur even in severe chronic pancreatitis, but the level of contrast enhancement compared with surrounding tissue is much lower in adenocarcinoma than in chronic pancreatitis [100]. Using specialized software to interpret contrast data, our results were confirmed in another study where time to peak (TTP) was associated with sensitivity of 93% and specificity of 89% [101].…”
Section: Contrast-enhanced Eusmentioning
confidence: 58%
“…Quantitative postprocedural assessment of uptake of the contrast agent has been proven useful to improve the accuracy of CE-EUS with low mechanical index for differentiating between the two entities [55,56].…”
Section: Contrast-enhanced Endoscopic Ultrasound (Ce-eus)mentioning
confidence: 99%